Experimental study of the kinetics of ligand-promoted dissolution of stibnite (Sb2S3) - Biver, Marc; Shotyk, William (Chemical geology, 2012)
Batch reactor experiments were carried out in order to investigate the influence of organic ligands in aqueous solution on the rate of dissolution of stibnite (Sb2S3). Ligands that may be regarded as representative of those occurring naturally in the soil solution were chosen, namely acetic, oxalic, citric, and salicylic acids, EDTA, glycine, cysteine, glucose, catechol, desferrioxamine-B, and standardized natural chestnut leaf litter extract. Millimolar concentrations of the ligands dissolved in inert buffers at pH=4, 6, and 8 were added to powdered stibnite in a stirred, thermostatted reactor (25°C) and the rate of increase in antimony concentration over time was monitored by ICP-OES. Dissolution rates were initially parabolic and settled into a linear regime. Comparison of initial and steady state rates achieved with different ligands with the blank experiments gives a very complex picture. Both rate enhancements and retardations are observed, and in some cases the net effect of a ligand at a given pH may be either an increased or a decreased mobilization with respect to the blank experiment, depending on the time of contact of the solution with the mineral. Rationalisations in terms of known principles of surface complexation are attempted. The extent of solution phase complexation of Sb(III) with the ligand under investigation is not found to be a decisive factor in the cases of those systems for which complexation constants are known. There is evidence suggesting that a linear free energy relationship may exist between the rates of ligand-promoted dissolution and pKa values of the ligands under investigation.